Asuhan Kebidanan Komprehensif Remaja pada Nn “A” dengan Flour Albus - Nur Afifah Harahap; Ardiana Batubara (Jurnal Kebidanan, 2023)
Adolescence is one of the phases in a growth and development process. Adolescent girls have very complex problems, namely reproductive problems related to hormones and reproductive functions, one of which is vaginal discharge. The purpose of this care is to provide comprehensive adolescent midwifery care to Mrs. "A" with vaginal discharge. The method of this care is continue of care. Data collection is done by interview and direct examination in accordance with health protocols. The subject of this care is Miss "A" aged 15 years with vaginal discharge at Patumbak Health Center, Deli Serdang Regency. The results of comprehensive midwifery care on Ms. "A", vaginal discharge experienced no longer exists. The conclusion of this comprehensive midwifery care by providing midwifery care independently and collaborating and handling early, no pathological vaginal discharge was found from the first visit to the last visit. It is recommended for midwives to continue counseling about vaginal discharge and proper vulva hygiene techniques.